Digital documentation of the Franciscan Observance architecture in Umbria. Preliminary surveys and analysis for conservation purposes - Bertocci, Stefano; Cioli, Federico (Restauro Archeologico, 2023)
This contribution focuses on one of the identified case studies of the Franciscan Observance architecture in Umbria, the convent of San Bartolomeo near Foligno (PG). It addresses the issue of heritage documentation methodology through integrated 3D laser scanner digital survey techniques and SfM/IM photogrammetry close range and UAV. The investigations aim at developing a preliminary diagnostic framework of the San Bartolomeo complex after the damage suffered in the 2016 earthquake in Central Italy. The research is part of the broader context of the three-year European project F-ATLAS – Franciscan Landscapes: The Observance between Italy, Portugal, and Spain, funded by the JPICH 2019 call. The Project aims at the census of the Franciscan Observance’s convents and their enhancement in a European dimension. The Project also tends to verify the state of conservation and the possibilities of a compatible development of reuse projects, trying to connect the building phenomenon within its territorial and cultural context.